Penerapan Standar Akuntansi Syariah Pada Koperasi Syariah Pinisi Sejahtera Mulia - Ramadhani, Laila Kamila; Anwar, Azwar; Azis, Fajriani (Jurnal Ilmiah Akuntansi dan Keuangan, 2024)
This research aimed: to analyze the application of sharia accounting standards at KSPPS Pinisi Sejahtera Mulia. The variables of this research is: the application of sharia accounting standards as a single variable. Sources of data in this study are divided into two parts, namely: primary data in the form of direct interviews and secondary data in the form of documentation. The data were collected by carried out using interviews and documentation techniques. The data obtained were analyzed using a qualitative descriptive analysis technique. The results of this study show that the presentation of financial reports at KSPPS Pinisi Sejahtera Mulia has not fully implemented PSAK 101. Meanwhile, the recording of murabahah accounting transactions, mudharabah accounting and ijarah accounting is in accordance with the provisions of PSAK 102, PSAK 105 and PSAK 107.